2021
DOI: 10.3390/ijerph18137066
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and the Impact on the Cranio-Oro-Facial Trauma Care in Italy: An Epidemiological Retrospective Cohort Study

Abstract: The coronavirus disease 2019 (COVID-19) has deeply modified the organization of hospitals, health care centers, and the patient’s behavior. The aim of this epidemiological retrospective cohort study is to evaluate if and how the COVID-19 pandemic has determined a modification in cranio-oro-facial traumatology service. Methods: The dataset included hospital emergency room access of a six-month pre-pandemic period and six months into pandemic outbreak. The variables collected were: patient age, gender, type of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 29 publications
(50 reference statements)
4
3
1
Order By: Relevance
“…Furthermore, this comparative study considered a full year of pandemic by evaluating the association of clinical and therapeutic variables. Although our findings are difficult to contrast with other previous reports due to the heterogeneity of the studies, with different time periods and disparity in the restriction measures applied according to each country, all studies indicated a clear decrease in cases of maxillofacial trauma ( 6 - 18 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, this comparative study considered a full year of pandemic by evaluating the association of clinical and therapeutic variables. Although our findings are difficult to contrast with other previous reports due to the heterogeneity of the studies, with different time periods and disparity in the restriction measures applied according to each country, all studies indicated a clear decrease in cases of maxillofacial trauma ( 6 - 18 ).…”
Section: Discussioncontrasting
confidence: 99%
“…In the study by Famà et al, as for the group of most urgency, the number of visits did not differ between prepandemic and pandemic phases [12]. This is consistent with our finding that the number of absolute emergencies was less affected during 2020.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with our finding that the number of absolute emergencies was less affected during 2020. The least-urgent cases of this study decreased like the relative emergencies in our study [12]. In the study by Guo et al a decrease of relative emergencies by more than 50% was noted, which again supports our observation [7].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A better understanding of cases’ and vaccines’ characteristics affecting the occurrence of oral lesions following anti-SARS-CoV-2 vaccine administration may enhance oral healthcare workers’ awareness and preparedness to comprehensively provide oral and dental care [ 47 , 48 , 49 , 50 , 51 , 52 ], as well as in interdisciplinary settings [ 53 , 54 , 55 , 56 , 57 , 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%